PROBLEMATICS OF ONLINE GAMBLING IN INDONESIA Structural Da'wah Approach - Fatuh Widoyo, Agus; Mastori; Arifin, Zenal (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Raden Fatah Palembang, 2024)
According to recent media reports, online gambling transactions have reached a critical point. The transaction totals reach hundreds of trillions of Rupiah and involve students, housewives, ordinary citizens, and state officials. As a result, issues like divorce, suicide, and murder emerge, endangering society. Various efforts have been made to combat the rise of gambling, particularly online gambling, including dawah bil lisan (oral preaching), education, and the eradication of gambling websites. However, online gambling demonstrates that the trend is still growing. Thus, the primary focus of this article is to discuss the structural Dawah perspective on comprehensively eliminating online gambling. This study aims to examine the phenomenon of online gambling and potential solutions within the structural dawah paradigm. This study used qualitative methods to analyze library data, such as verified and relevant books, journals, and online news sources. The results of this study reveal that structural Dawah can be an essential solution to eradicating online gambling because the structural position of the government has the power and strength to regulate and prohibit online gambling by the principles of Dawah.